Cellular responses to thermal stress and moderate oxygen limitation in juvenile lake trout - Alyssa M. Weinrauch; Analisa Lazaro‐Côté; Travis C. Durhack; Eva C. Enders; Ken M. Jeffries (Journal of Fish Biology, 2025)
Lake trout ( Salvelinus namaycush ) is an important food fish in northern communities, inhabiting cool, well‐oxygenated water, but climate change is reducing available habitat, with extended summer stratification of lakes creating an upper thermal barrier (~15°C) and lower dissolved oxygen (DO) boundary (4–7 mg L −1 ). Together, these environmental factors can influence tolerance thresholds and climate change may lead to abiotic factors exceeding these physiological thresholds in lake trout habitats. Thresholds can shift with environmental acclimation in lake trout populations, but the functional basis of this shift has yet to be examined. The abundance of transcripts offers insight into underlying cellular responses to environmental stressors that can provide an early warning of adverse physiological outcomes. Here, we used a stress‐response transcriptional profiling chip to investigate a suite of genes involved in thermal and general stress in lake trout acclimated to a range of temperatures (6–18°C) and two DO conditions (~10 or ~6 mg L −1 ), as well as following acute thermal stress (i.e. CT max ). Transcriptional profiles were assessed in the gill, liver and epidermal mucus. Generally, fish acclimated to the greatest combined stressor (i.e. 18°C and 6 mg L −1 DO) had the largest transcriptional response, suggestive of a transition from a routine stress response to an extreme survival response. A noted temperature dependence occurred in liver tissue, which was not evident in gill or mucus tissues. Further, transcriptional responses in the gill and mucus were highly correlated ( r = 0.74–0.87), highlighting the potential use of these tissues for non‐lethal sampling methods to enhance management and conservation strategies for lake trout.

Sub‐lethal temperature thresholds indicate acclimation and physiological limits in brook trout Salvelinus fontinalis - Scott M. Morrison; Theresa E. Mackey; Travis Durhack; Jennifer D. Jeffrey; Lilian M. Wiens; Neil J. Mochnacz; Caleb T. Hasler; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Journal of Fish Biology, 2020)
The upper thermal tolerance of brook trout Salvelinus fontinalis was estimated using critical thermal maxima (CT max ) experiments on fish acclimated to temperatures that span the species' thermal range (5–25°C). The CT max increased with acclimation temperature but plateaued in fish acclimated to 20, 23 and 25°C. Plasma lactate was highest, and the hepato‐somatic index ( I H ) was lowest at 23 and 25°C, which suggests additional metabolic costs at those acclimation temperatures. The results suggest that there is a sub‐lethal threshold between 20 and 23°C, beyond which the fish experience reduced physiological performance.